محمد مسعودي . عبد الغني دادن . - محمد مسعودي . عبد الغني دادن . (جامعة الوادي - University of Eloued, 2015)
لقد أصبح واضحا أن المكاسب التى تترتب على اى نشاط اقتصادى ضار بالبيئة يكون قصير المدى ويعتبر قطاع المحروقات أولى هذه النشاطات، لذلك كان لابد من إيجاد توازن بين تحقيق مزيد من التنمية الاقتصادية والمحافظة على البيئة فى إطار استغلال قطاع المحروقات بالجزائر، حيث شهدت السنوات الأخيرة قلقا متزايدا من جراء عملية التنمية المعتمدة على قطاع المحروقات خاصة من حيث انبعاثات غازات الاحتباس الحراري، وتنقسم عملية استغلال قطاع المحروقات الى مرحلتي المنبع والمصب، و في هذه الدراسة حللنا أثر مرحلة المنبع في انبعاث ثاني أكسيد الكربون بالجزائر باستخدام أدوات الدراسة القياسية للفترة 2000-2010 والتي أثبتت عدم تأثير مرحلة منبع قطاع المحروقات في انبعاث ثاني أكسيد الكربون بالجزائر مما يثبت أن مرحلة المنبع والتي تنحصر في اسكشاف واستخراج النفط والغاز صديقة للبيئة من حيث انبعاث ثاني أكسيد الكربون. It has become clear that the gains that have on any economic activity harmful to the environment will be short-term and is considered the hydrocarbon sector first of these activities, so it was necessary to find a balance between achieving greater economic growth and preservation of the environment in the context of the exploitation of the hydrocarbon sector in Algeria, where recent years have seen concern increasing as a result of the development process based on the hydrocarbon sector, especially in terms of greenhouse gas emissions, and the process is divided exploit the hydrocarbon sector to the two phases of the upstream and downstream, and in this study we analyzed the effect of stage upstream in the emission of carbon dioxide in Algeria using the tools of the study standard for the period 2000-2010, which proved to be the source of the impact phase of the hydrocarbon sector in the emission of carbon dioxide in Algeria, which proves that the phase of the upstream-friendly environment in terms of carbon dioxide emissions
مقال
Keywords: مرحلة المنبع، قطاع المحروقات، انبعاث ثاني أكسيد الكربون، دراسة قياسية; upstream stage, the hydrocarbon sector, the emission of carbon dioxide, the study record